PERANCANGAN SISTEM MANAGEMENT GUDANG BERBASIS WEB DENGAN EXTREME PROGRAMMING - Mangapul Siahaan; Sudy (JURNAL ILMIAH BETRIK, 2023)
Information technology has become very important in the dissemination and reception of information, especially through web-based media, in an era of increasingly advanced and modern technology. Both organizations and individuals need information technology to increase efficiency and effectiveness in various aspects of operations and services provided. Warehouse management has become essential for an effective supply chain in an increasingly competitive business world. Business operations are greatly influenced by warehouse management, which plays a vital role in the storage, management, and distribution of goods. Although web-based warehouse management systems allow real-time monitoring, the main problem is responding to frequently changing requirements. To overcome this problem, this research uses the Extreme Programming (XP) method, an approach that is highly responsive and suitable for constantly changing environments and unstable customer needs. The XP method enables close collaboration between warehouse owners, suppliers and developers, ensuring that the software developed is of high quality. This research found a web-based warehouse management application system that can help companies and MSMEs manage their warehouses better. Management of goods, suppliers, ordering goods, transactions, reports and products and several important features in this system. Blackbox testing methods have ensured that all features function properly, increasing confidence in the use of the system. This study helps us understand how information technology can help improve warehouse management in a dynamic and competitive business context. With the help of information technology and XP methods, warehouse management becomes more responsive, flexible and able to better meet customer requirements. This is an important step towards success in the rapidly evolving business world.